2015
DOI: 10.1159/000431000
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effectiveness and Prognostic Factors of Intravitreal Ranibizumab between Typical Neovascular Age-Related Macular Degeneration and Polypoidal Choroidal Vasculopathy over 24 Months of Follow-Up

Abstract: Purpose: To compare the response to ranibizumab between patients with typical neovascular age-related macular degeneration (tAMD) and those with polypoidal choroidal vasculopathy (PCV), and to determine the predictors for the outcomes. Methods: Fifty-nine eyes from 59 consecutive patients (tAMD: 27 eyes, PCV: 32 eyes) were treated with three monthly ranibizumab injections followed by as-needed retreatment. Best-corrected visual acuity (BCVA) and morphological parameters were evaluated over 24 months of follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Retrospective analysis of medical records from patients with nAMD treated with ranibizumab supports these phase 3 data, with a Pearson correlation test identifying increasing age as significantly associated with a worse visual prognosis at month 12 for patients with nAMD ( p = 0.02), but interestingly not those with polypoidal choroidal vasculopathy (PCV; p > 0.22) [ 21 ]. However, a separate retrospective interventional cohort study of ranibizumab treatment showed an association between age and response at month 24 in patients with PCV ( p = 0.03), but not those with nAMD ( p = 0.87) using univariate logistic analyses [ 22 ]. Age at baseline was also identified as a predictor of VA response at 3 to 12 months in retrospective analyses of patients receiving bevacizumab [ 23 25 ] and ranibizumab [ 26 ].…”
Section: Baseline Factors That Predict Functional and Anatomical Rmentioning
confidence: 99%
“…Retrospective analysis of medical records from patients with nAMD treated with ranibizumab supports these phase 3 data, with a Pearson correlation test identifying increasing age as significantly associated with a worse visual prognosis at month 12 for patients with nAMD ( p = 0.02), but interestingly not those with polypoidal choroidal vasculopathy (PCV; p > 0.22) [ 21 ]. However, a separate retrospective interventional cohort study of ranibizumab treatment showed an association between age and response at month 24 in patients with PCV ( p = 0.03), but not those with nAMD ( p = 0.87) using univariate logistic analyses [ 22 ]. Age at baseline was also identified as a predictor of VA response at 3 to 12 months in retrospective analyses of patients receiving bevacizumab [ 23 25 ] and ranibizumab [ 26 ].…”
Section: Baseline Factors That Predict Functional and Anatomical Rmentioning
confidence: 99%
“…25 Although ranibizumab, bevacizumab, and aflibercept have all demonstrated efficacy in improving vision, decreasing foveal thickness, and causing polyp regression in patients with PCV, [26][27][28] ranibizumab therapy may be more effective in eyes with typical nAMD than in eyes with PCV. 8 In the BAMBOO study, abicipar had beneficial effects on BCVA and CRT in both patients with PCV and patients with typical nAMD.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, subtypes of nAMD that have been identified (typical nAMD, polypoidal choroidal vasculopathy [PCV], and retinal angiomatous proliferation) appear to differ in their responsiveness to anti-VEGF treatment. [7][8][9] In a cross-sectional, retrospective study, most patients diagnosed with nAMD who demonstrated a poor response to ranibizumab had atypical nAMD, with the majority having PCV. 10 These results suggest a need for novel treatments for nAMD that require less-frequent administration (decreasing the burden of treatment) and that are effective in atypical subtypes of nAMD lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have demonstrated that PCV showed a good visual outcome with IVR [6,7,18] , but it is also known that certain PCV cases exhibited poor response to IVR [10,19] although the reasons were unknown. In the present study, type 1 PCV classified by the presence of clear BVN with polypoidal lesions showed a good visual outcome of IVR, but type 2 PCV did not show any improvement in mean BCVA.…”
Section: Discussionmentioning
confidence: 99%